2010
DOI: 10.1021/bi101056m
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Hydrolysis of Organophosphate Nerve Agents by the Bacterial Phosphotriesterase

Abstract: Organophosphorus compounds include many synthetic, neurotoxic substances that are commonly used as insecticides. The toxicity of these compounds is due to their ability to inhibit the enzyme acetylcholine esterase. Some of the most toxic organophosphates have been adapted for use as chemical warfare agents; the most well known are GA, GB, GD, GF, VX and VR. All of these compounds contain a chiral phosphorus center with the S P -enantiomers being significantly more toxic than the R P -enantiomers. Phosphotriest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
169
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(176 citation statements)
references
References 20 publications
2
169
1
Order By: Relevance
“…This stereoselectivity is opposite to that observed for wild-type PTE (33). The organophosphate and organophosphonate esters are toxic because of their ability to rapidly inactivate the enzyme acetyl cholinesterase.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This stereoselectivity is opposite to that observed for wild-type PTE (33). The organophosphate and organophosphonate esters are toxic because of their ability to rapidly inactivate the enzyme acetyl cholinesterase.…”
Section: Discussioncontrasting
confidence: 87%
“…From the time course for the hydrolysis of racemic 6 by PTE alone (Figure 4B) and Pmi1525 alone (Figure 4C) it can be concluded that Pmi1525 and PTE preferentially hydrolyze the opposite enantiomers from one another. Since PTE hydrolyzes the ( R P )-enantiomer of isobutyl 4-acetylphenyl methylphosphonate ( 9 ) 25 times faster than the ( S P )-enantiomer ( 10 ), Pmi1525 prefers to hydrolyze the ( S P )-enantiomer of this substrate (33). For wild-type PTE, the ( R P )-enantiomer of compound 6 is hydrolyzed 75 times faster than the ( S p )-enantiomer based on a fit of the data in Figure 4B to the sum of two exponentials (29).…”
Section: Resultsmentioning
confidence: 99%
“…7,22 The individual enantiomers of p-acetophenyl VR (APVR) were synthesized as previously described. 16 Samples of VX and VR were Chemical Agent Standard Analytical Reference Material of the 8 highest purity available, and were further purified as described previously. 7 Unless otherwise noted, all other chemicals were purchased from Sigma Aldrich.…”
Section: Materials Growth Media and Antibiotics Were Procured From Rmentioning
confidence: 99%
“…Wild-type PTE has enzymatic activity for the hydrolysis of racemic VR similar to VX, but the larger isobutyl group attached to the phosphorus center results in a 25-fold preference for the RPenantiomer. 16,19 The catalytic activity of wild-type PTE for the hydrolysis of the SPenantiomer of VR (kcat/Km = 4.3 M -1 s -1 ) is significantly lower than for the hydrolysis of VX.…”
mentioning
confidence: 99%
See 1 more Smart Citation